PENERAPAN PEMBELAJARAN TAHFIDZ DALAM MENINGKATKAN HAFALAN AL-QUR’AN SISWA - Sirulhaq, Sekarmaji; Rahmawati, Siti; Acip; Khutomi, Budi Munawar (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2025)
This research was motivated by the researcher's interest in the application of tahfidz learning (memorization of the Qur'an) at MI Qur'an Al-Qudwah Palabuhanratu. Obstacles in learning tahfidz in elementary schools include differences in students' memory abilities, students' laziness, and tendencies to play. MI Qur'an Al-Qudwah Palabuhanratu runs a tahfidz learning program that involves tahfidz teachers and all class teachers. The purpose of this study was to describe how the application of tahfidz learning improves students' memorization of the Qur'an at MI Qur'an Al-Qudwah Palabuhanratu. This research is a qualitative research conducted at MI Qur'an Al-Qudwah Palabuhanratu. Data was collected through observation, in-depth interviews and documentation. Data is analyzed by reducing, displaying, and drawing conclusions. The validity of the data is checked through triangulation of data sources and techniques, and combining them with theory. The results of the study show several things: (1) The program for implementing tahfidz learning includes tahfidz subjects, muraja'ah, BTQ (Reading and Writing Qur'an), Al-Qur'an sima'an program, and munaqasyah assembly. (2) Tahfidz learning activities take place on Monday-Thursday. Grades I, II, and III carry out in the morning before class begins, while grades IV and V in the afternoon before going home. The methods used are different, such as the sama'i and jama' methods for grades I, II, and III, as well as the bin nadzar and tahfidz methods for grades IV and V. Memorizing material also varies according to the juz of the Qur'an. (3) The actions taken in implementing tahfidz learning include the tahfidz teacher's suggestion to students who have difficulty achieving targets to practice more at home with the help of their parents. Daily evaluations are also carried out to monitor student memorization progress. Through this program, research shows that there are efforts to improve students' memorization of the Qur'an by involving various methods and activities at MI Qur'an Al-Qudwah Palabuhanratu.